2016
DOI: 10.1155/2016/7986234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Negative Pressure on Proliferation, Virulence Factor Secretion, Biofilm Formation, and Virulence-Regulated Gene Expression ofPseudomonas aeruginosaIn Vitro

Abstract: Objective. To investigate the effect of negative pressure conditions induced by NPWT on P. aeruginosa. Methods. P. aeruginosa was cultured in a Luria–Bertani medium at negative pressure of −125 mmHg for 24 h in the experimental group and at atmospheric pressure in the control group. The diameters of the colonies of P. aeruginosa were measured after 24 h. ELISA kit, orcinol method, and elastin-Congo red assay were used to quantify the virulence factors. Biofilm formation was observed by staining with Alexa Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…The same activity of pyocyanin inhibition has been found in Terminalia chebula extract [52]. Ex vivo result showed that elastase producing isolates of P. aeruginosa significantly aid in damaging the skin and wound by degrading the skin proteins [53] and thus aid in the pathogenicity. Hence, elastase assay was also performed.…”
Section: Discussionsupporting
confidence: 65%
“…The same activity of pyocyanin inhibition has been found in Terminalia chebula extract [52]. Ex vivo result showed that elastase producing isolates of P. aeruginosa significantly aid in damaging the skin and wound by degrading the skin proteins [53] and thus aid in the pathogenicity. Hence, elastase assay was also performed.…”
Section: Discussionsupporting
confidence: 65%
“…P. aeruginosa motility under different negative pressure (NP) and atmospheric pressure (AP) conditions were evaluated. The bacterial culture protocol was based on our previously published model for the in vitro NP condition and motility medium was prepared as previously described with a few modifications (Rashid and Kornberg 2000 ; Wang et al 2016 ). Briefly, a NP condition was created for bacterial growth and an air tight chamber was used as the incubator.…”
Section: Methodsmentioning
confidence: 99%
“…However, investigations regarding the influence of NPWT on biofilms, virulence factors and motility remain limited. Previously, we demonstrated that negative pressure induced by NPWT could change bacteria biofilms and secretion in vitro (Li et al 2015 ; Wang et al 2016 ). The present study aimed to evaluate the potential effect of NPWT on P. aeruginosa motility in vitro, and biofilms and virulence factors in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…It reduced the gene expression [ 175 ]. This influence is vital, as exotoxin A impedes wound healing, and alleviating its control is beneficial [ 176 ]. Meanwhile, the genetic upregulation of tissue repair and collagen deposition is pursued by bactericidal zinc-doped Prussian blue nanocubes.…”
Section: Nanoplatforms Against Wound Biofilmsmentioning
confidence: 99%